A insegurança jurídica decorrente da livre disposição: cláusulas Earn-out e a necessidade de mediação e arbitragem desencadeada pela ausência de previsão legal. - Teófilo, João Vitor Simões (2024)
The earn-out clause is a contractual mechanism primarily present in mergers and acquisitions of companies. Its use makes negotiations more flexible by bringing the desired values of the parties closer together, conditioning a portion of the asset to the fulfillment of future goals, usually related to the company’s performance. However, despite assisting in the conclusion of the legal transaction, the contractual freedom to set the goals for its fulfillment demonstrates the possibility of opportunistic behaviors that may harm the other party. This represents a moral hazard, arising from good faith, linked to the subjective aspect of the contract and the will of the parties, which can cause legal uncertainty for individuals, precisely due to the absence of specific legal provisions. The main objective of this work is to present the risks arising from the lack of specific regulation and the consequent freedom to dispose of earn-out clauses, which provides legal uncertainty and a higher occurrence of judicial disputes. Additionally, it aims to demonstrate extrajudicial methods that help reduce such conflicts, specifically mediation and arbitration. The method used was bibliographic research, through doctrinal theses involving the subject, as well as the analysis of concrete cases and research. Thus, the main points regarding the use of the earn-out clause, especially in the business context, were exposed, as well as the use of mediation and arbitration to mitigate disputes. At the end of the work, it was concluded that, as long as there is no specific regulation on the use of the earn-out clause, the drafting of these contracts should be done in a way that addresses each point related to it. In the event of any dispute, it is recommended to use extrajudicial methods, due to their speed and specialization in the subject, thus contributing to the resolution of these conflicts.